Collaborative Filtering Based Recommender Systems For Marketplace Applications - Witriana Endah Pangesti; Rachmat Suryadithia; Priyono; Muhammad Faisal; Bilal Abdul Wahid; Arman Syah Putra (International Journal of Educational Research & Social Sciences, 2021)
The background of this research is to give the best advice to users who still don't know about other marketplaces that they can still use, to find the items they are looking for and at a cheaper price or with promos they can get. The method used in this research is to use a trial based on data obtained from users who use the media marketplace to purchase an item, with this, the real data can be known so that the best advice for an unknown marketplace can be given. In how many countries, a recommender system has been implemented in a marketplace that will provide advice using advertising media on social media, by using social media, users can find out about the marketplace, and are given continuous advice to install the application so that they can make transactions with purchase of a product in the marketplace. The purpose of this research is to give the best advice so that all people, especially marketplace users, can find out which other marketplaces are in order to know and be able to shop at other marketplaces, by doing price comparisons and being able to get promo prices and knowing based on habits, and ratings from the marketplace.